Safety and Pitfalls of Blepharoptosis Surgery in Elderly People - Shirakawa, Yuji; Uemura, Kazuhisa; Kumegawa, Shinji; Ueno, Kazuki; Iwanishi, Hiroki; Saika, Shizuya; Asamura, Shinichi (Archives of Plastic Surgery, 2023)
Background Elderly patients often have complications of blepharoptosis surgery that can result in the appearance or exacerbation of superficial punctate keratopathy (SPK). However, postoperative changes to SPK status have not been previously reported. We used subjective assessment of symptoms and measurement of SPK scale classification to investigate the safety and efficacy of blepharoptosis surgery in elderly patients.Methods Included in this prospective study were 22 patients (44 eyes) with bilateral blepharoptosis that underwent surgery. Patients comprised 8 males and 14 females with a mean (±standard deviation) age of 75.7 ± 8.2 years (range: 61–89). Blepharoptosis surgery consisted of transcutaneous levator advancement and blepharoplasty including resection of soft tissue (skin, subcutaneous tissue, and the orbicularis oculi muscle). Margin reflex distance-1 (MRD-1) measurement, a questionnaire survey of symptoms and SPK scale classification, was administered preoperatively and 3 months postoperatively for evaluation.Results The median MRD-1 was 1 mm preoperatively and 2.5 mm postoperatively, representing a significant postoperative improvement. SPK area and density scores were found to increase when the MRD-1 increase was more than 2.5 mm with surgery. All 10 items on the questionnaire tended have increased scores after surgery, and significant differences were observed in 7 items (poor visibility, ocular fatigue, heavy eyelid, foreign body sensation, difficulty in focusing, headaches, and stiff shoulders).Conclusion Blepharoptosis surgery was found to be a safe and effective way to maintain the increase in MRD-1 within 2.0 mm. Despite the benefits, surgeons must nonetheless be aware that blepharoptosis surgery is a delicate procedure in elderly people.
Keywords: blepharoptosis; elderly patients; superficial punctate keratopathy; margin reflex distance-1; subjective symptoms